Estudos etológico e químico dos feromônios de trilha de marcação de território de Atta opaciceps Borgmeier, 1939 (Hymenoptera: Formicidae) - Campos, Rousseau da Silva (2012)
The leaf-cutting antsof the genus Atta and Acromyrmex belong to the order Hymenoptera, Formicidae family, Myrmicinae subfamily and Attini tribe are locatedin the Americas, occurring in tropical areas of Mexico andin Central and South America,are considered herbivorous and difficult to control when attacking crops and forests. The species Atta texana and Acromyrmex versicolor are the only representatives of these ants foundin North America. Several species of the genus Attaare found in Brazil. Understanding the behavior of leaf-cutting ants in their multiple division of laboris a necessary step to establish living with them, and develop or adapt new methods of control, when these reach the economic injury level. There fore, this study sought to clarify the behavior of Atta opaciceps regarding the specificity of behaviors of territory marking and trail, seeing how the different castes respond to different intra and interspecific extracts (Acromyrmex subterraneus subterraneus, A. cephalotes, A. sexdens sexdens and A. sexdens rubropilosa) on laboratory conditions. It also sought to identify the chemical constituents present in the foragers venom gland extracts of A.opaciceps, seeking to know what the compounds responsible fore liciting the trail behavior of foragers of this species.